Energy Retrofitting of the Mediterranean Terrace Dwellings - Despina Serghides; Marina Markides; Martha Katafygiotou (Renewable Energy and Sustainable Development)
The building sector in Europe is responsible for an estimated 40% of the total energy consumption. It is well established that the reduction of building energy consumption necessitates energy efficient renovation of the existing buildings. In order to achieve this objective it is necessary to document the existing building stock. This paper focuses on the existing terrace housing in the Mediterranean region and specifically in Cyprus. The processing of the statistical data was carried out and the building typologies were developed based on a harmonised structure for European building typologies according to the IEE EPISCOPE project. A representative terrace housing complex, of the corresponding building typology, was used as showcase for demonstrating the energy performance and the potential of energy savings, by applying energy conservation measures (ECMs). Three units of different location in the terrace building complex were selected to carry out comparative studies for their energy performance and classification. The effectiveness of the strategies and the techniques towards minimising the energy consumption are simulated with the use of iSBEMcy tool. This is the official used for the categorization of energy efficiency in buildings, according to the European Directive 2002/91/EC. The study utilises information from the database, of the thermal characteristics of the building envelope and of the electromechanical systems, which was developed by the European, IEE Episcope Project, for the terrace residential buildings. This research aims to fill in the current knowledge gap of the energy-related characteristics of the specific building typology. Building typologies can be a useful instrument to facilitate the energy performance assessment of the building stock.